2018
DOI: 10.1155/2018/5047526
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Autophagy in Acute Lung Injury Induced by Myocardial Ischemia Reperfusion in Diabetic Rats

Abstract: Patients with diabetes are vulnerable to myocardial ischemia reperfusion (IR) injury, which may also induce acute lung injury (ALI) due to overaccumulation of reactive oxygen species (ROS) and inflammation cytokine in circulation. Despite autophagy plays a significant role in diabetes and pulmonary IR injury, the role of autophagy in ALI secondary to myocardial IR in diabetes remains largely elusive. We aimed to investigate pulmonary autophagy status and its roles in oxidative stress and inflammation reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…Autophagy inhibition by 3-MA with dosage of 15 mg/kg/d i.p. is consistent with studies in the rat models 60,61 . The sham group was injected with an equal volume of saline as a control.…”
Section: Animals and Treatmentsupporting
confidence: 92%
“…Autophagy inhibition by 3-MA with dosage of 15 mg/kg/d i.p. is consistent with studies in the rat models 60,61 . The sham group was injected with an equal volume of saline as a control.…”
Section: Animals and Treatmentsupporting
confidence: 92%
“…When the stress stimuli remain unresolved, continued autophagy activation progresses to autophagy defect which is associated with the development of metabolic syndrome, lipid abnormalities, and diabetes [40]. Evidence from our group [26, 45], as well as others [44, 46], have demonstrated that autophagy is inhibited in diabetic state. Autophagy also plays an important role in the pathogenesis of cerebral I/R injury [47].…”
Section: Discussionmentioning
confidence: 99%
“…Light microscopic examination was conducted to determine the following: i) Pulmonary interstitial edema; ii) airway epithelial injury; iii) the degree of hyalinization; and vi) the lung injury score. The criteria for the lung injury score was membrane formation, neutrophil infiltration and alveolar hemorrhage (7,19). The indices were graded as follows: i) normal=0'; ii) minimal change=1'; iii) mild change=2'; iv) moderate change=3'; and v) severe change=4'.…”
Section: Establishment Of Myocardial I/r Injurymentioning
confidence: 99%
“…Several studies have also demonstrated the subclinical significance of the diabetic lung, and that patients with diabetes are prone to severe respiratory disorders in the event of acute or chronic lung and/or cardiac disease (2,5). Further clinical and experimental data have indicated that inflammatory responses and metabolic abnormalities in diabetes aggravate the acute lung injury (ali) via autophagy (6,7). Myocardial infarction is considered to be one of the more common complications underlying diabetes-associated mortality.…”
Section: Introductionmentioning
confidence: 99%